Immigration Trends After 20 Years of NAFTA - Mónica Verea (Norteamérica)
The twentieth anniversary of nafta is an opportunity to reflect on what has happened to migration flows. In this essay, the author gives an overview of the trends of Mexican legal high- and low-skilled migration flows as well as of unauthorized flows to the United States, which have increased significantly during the last 20 years, contrary to original expectations. She takes Mexican migration to Canada as a reference for comparison since the flows are less dynamic. Finally, she also analyzes the significant increase of foreigners entering Mexico and the new phenomenon of “return migration.”